Lung cancer and end-of-life care: a systematic review and thematic synthesis of aggressive inpatient care. Issue Volume 9: Issue (2019)Supplement 4 (31st August 2019) - Bylicki, Olivier; Didier, Morgane; Riviere, Frederic; Margery, Jacques; Grassin, Frederic; Chouaid, Christos
Abstract : Objectives: Despite recent advances in thoracic oncology, most patients with metastatic lung cancer die within months of diagnosis. Aggressiveness of their end-of-life (EOL) care has been the subject of numerous studies. This study was undertaken to evaluate the literature on aggressive inpatient EOL care for lung cancer and analyse the evolution of its aggressiveness over time. Methods: A systematic international literature search restricted to English-language publications used terms associated with aggressiveness of care, EOL and their synonyms. Two independent researchers screened for eligibility and extracted all data and another a random 10% sample of the abstracts. Electronic Medline and Embase databases were searched (2000–20 September 2018). EOL-care aggressiveness was defined as follows: 1) chemotherapy administered during the last 14 days of life (DOL) or new chemotherapy regimen during the last 30 DOL; 2) >2 emergency department visits; 3) >1 hospitalisation during the last 30 DOL; 4) ICU admission during the last 30 DOL and 5) palliative care started <3 days before death. Results: Among the 150 articles identified, 42 were retained for review: 1 clinical trial, 3 observational cohorts, 21 retrospective analyses and 17 administrative data-based studies. The percentage of patients subjected to aggressive therapy seems to have increased over time. Early management by palliative care teams seems to limit aggressive care. Conclusions: Our analysis indicated very frequent aggressive EOL care for patients with lung cancer, regardless of the definition used. The extent of that aggressiveness and its impact on healthcare costs warrant further studies.